ASSOCIATIONS OF CHILDHOOD TRAUMA AND ADULT RESILIENCE WITH HIPPOCAMPAL VOLUME IN LATE MIDLIFE. (11th November 2018) - Franz, C; Stevens, S; Hernandez, J; Tai, C; Slayday, R; Kremen, W
Abstract: Based on theories of adult development, Helson and Srivastava (2001) developed a model of different adult development pathways. Using data from 1199 participants in the Vietnam Era Twin Study of Aging, we examined associations between adult development paths in men exposed to childhood trauma and hippocampal volume in late midlife. We predicted trauma-exposed men in the low-resilience group would have smaller hippocampal volume. Like Helson and Srivastava, we defined four groups based on two sub-scales from the Ryff Psychological Well-Being Scale. Environmental mastery (EM) assesses effectiveness in the outer world (EM) and personal growth (PG) evaluates intrapsychic development. Being low in both EM and PG ("depleted") reflects low resilience while being high on both reflects optimal adjustment. Participants with only high EM are considered "conservers" while those with only high PG are "seekers." Men exposed to childhood trauma (65%) were significantly more likely to be in the depleted group (26%) than non-exposed men (18%). 39% of trauma-exposed men were highly resilient, 15% being "seekers" and 22% "conservers." In comparison, 42% of non-trauma exposed men were highly resilient, 12% and 28% were considered "seekers" and "conservers", respectively. Mixed models revealed no main effect of resilience on hippocampal volume [F(3, 161) = 0.59 p=0.62]; a significant effect of childhood trauma F(1, 161)=4.39 p=.04; and a significant resilience-by-trauma interaction F(3, 161) = 2.80 p=.04. Childhood trauma was associated with smaller hippocampal volume, which was smallest in trauma-exposed, non-resilient men. These results suggest potential significance of early trauma exposure and resilience characteristics for neurological aging.